HUBUNGAN SIKAP PEDULI LINGKUNGAN DENGAN KEMAMPUAN PEMAHAMAN KONSEP IPA SISWA KELAS lll SDN 84 SINGKAWANG - Eka Murdani; Trigasari, Salamah; Sumarli; Kamaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT This research aims to: (1) describe the level of environmental concern of class III students at SDN 84 Singkawang; (2) describe the level of ability to understand science concepts of class III students at SDN 84 Singkawang; (3) determine the relationship between environmental care attitudes and the ability to understand science concepts of class III students at SDN 84 Singkawang. This research method is quantitative research with a correlation approach. The population of this study were all class III students at SDN 84 Singkawang. The sampling technique in this research is a saturated sampling technique. The sample in this study was all class III students at SDN 84 Singkawang consisting of class IIIA and IIIB totaling 46 students. The data collection techniques in this research are test and non-test techniques, tests of students' ability to understand science concepts on material about loving plants and animals and non-test techniques of environmental care attitude questionnaires. The data analysis techniques used in the research are descriptive percentage analysis, average value analysis, and Spearman Rank correlation. The results of the research show that (1) the level of students' environmental care attitude is relatively high with an overall average score of 60.97 or a percentage of 61% (2) the level of students' ability to understand science concepts is relatively high with an overall average of 69.81 or with percentage 70% (3) there is a relationship between environmental care attitudes and students' ability to understand science concepts with tcount > ttable = 5.35 > 1.68 and a coefficient of determination of 0.349 or a percentage of 39.40%. So it can be concluded that there is a relationship between an attitude of caring for the environment and the ability to understand science concepts in class III students at SDN 84 Singkawang. Keywords: environmental care attitude, ability to understand concepts